Design of a pneumatic system for the development of skills among aeronautics maintenance technology students - Calderón Pérez, Jorge Luis; Cruz Rico, Oliver; Ospina Martínez, Darwin (Ingeniería Solidaria, 2016)
Introduction: This article is the result of the “Design and installation of a pneumatic system for Aeronautics Maintenance Technology students’ instruction (TMA)”. The research was conducted during 2014 and 2015 by the Police Aviation School research group (esavi), attached to the National Directorate of Schools (DINAE).Methodology: design and construction of a lab with a pneumatic system for handling aviation materials and structures by the Aeronautics Maintenance Technology students. The pneumatic network in galvanized steel was used with a first generation Quincy compressor that the National Police has in the hangar of Mariquita, Colombia. For the construction and installation, laws that analyzed the behavior of gases applied in the installation of the existing pneumatic network had to be studied.Results: the pneumatic system was installed as a teaching tool in order to improve the skills of knowledge to students. The pneumatic system created maintained constant pressure between 90-100 psi at the six work points adapted in the pneumatic system required for the operation of the tools used in the aviation field.Conclusions: the classroom designed allowed simulating actual working conditions to ensure that students gain the skills for future job performance
Keywords: aeronautics; classroom practice; design; maintenance; pneumatic system